Modeling and analyses of energy performances of photovoltaic greenhouses with sun-tracking functionality. (1st January 2019) - Gao, Yuan; Dong, Jianfei; Isabella, Olindo; Santbergen, Rudi; Tan, Hairen; Zeman, Miro; Zhang, Guoqi
Graphical abstract: Highlights: Dynamic photovoltaic (PV) greenhouses with various PV densities are modeled. Energy performance under different sun-tracking methods is analyzed. No-shading sun tracking improves the performance of high-density PV greenhouses. Mixed sun-tracking schemes can balance the production of food and electricity. Abstract: Dynamic photovoltaic (PV) greenhouses integrate sustainable energy generation with plant cultivation, offering more possibilities of energy production and microclimate control by adjusting the sun-tracking angles. Previous studies on PV greenhouses barely paid attention to the PV partial shading effects, and rarely recorded the performance across the full range of rotation angles. In this study, we first build computer simulation models of typical greenhouses with high-density (1/2 roof area) and low-density (1/3 and 1/4 roof area) PV layouts. Then four special sun-tracking positions are found in the model of equivalent global irradiance, which is defined as the quotient of the total input power divided by the area of PV module under partial diffuse shadows. Simulation models are also built in terms of PV modules and interior irradiance. Simulations are conducted using the climate data of Delft, the Netherlands ( 52.01 ° N, 4.36 ° E ). Results show that high-density PVs under no-shading sun tracking generate 6.91% more energy than that under conventional (quasi-perpendicular) sun-tracking. Meanwhile, no-shading sun tracking allows more diffuse sunlight to enter the greenhouse mounted with high-density PV panels, resulting in 10.96% and 10.68% improvement on the annual average global irradiance and uniformity on the target plane compared to the fixed PV panels in the closed position. Regarding low-density PV layouts, which barely suffer from partial shading problems, quasi-perpendicular sun tracking improves the annual energy generation by 7.40% relative to the closed position. However, the average global irradiance reaches the minimum in this position because more sunlight is blocked by PVs. Meanwhile, the average uniformity of global irradiance reveals good (but not the best) performance, resulting in up to 9.80% (1/3 coverage) and 4.70% (1/4 coverage) improvement respectively compared to the closed position. The proposed methods and simulation results provide guidelines for the initial design and daily operation of PV greenhouses, aiming to balance the PV power generation and food production.